An effectiveness study on incorporating gagne's nine events in computer programming easy-to-read text at Centre for Foundation Studies, International Islamic University of Malaysia - Bakar, Noor Hasrina; Idris, Mohd Norhaedir; Hassan, Noor Azimah (2012)
Centre for Foundation Studies is a direct feeder to the undergraduate program at International Islamic University of Malaysia (IIUM). SEF1514/ IFF1444 – C Programming is one of the required subjects for Sciences Programme students to pass. This paper discusses the identified challenges that lead to unfavourable performance among the foundation students who enrolled in C Programming course, and the proposed method to overcome these. Few scholars mentioned that students’ main weaknesses in programming subjects are their lack of problem solving capability and insufficient analytical thinking skill [1] & [2]. Mitra, in her work, mentioned that most students feel that programming is a challenging intellectual exercise [3]. In addition to the above-mentioned problems with learning computer programming, we also found out that foundation students have difficult time dealing with the materials used for the course. To them, computer programming textbooks are too burdensome, and too complex to understand. From the study conducted here at IIUM, good and comprehensive materials seemed to be costly, and most of the students (majority are non-computer related majors) opted not to purchase the materials, and relied mostly on lectures during class meetings. As an initiative to improve the students’ performance in the course, a group of lecturers teaching C Programming at the centre came out with an Easy-to-Read textbook that followed closely Robert Gagne’s Nine Events of Instructions. Gagne is considered to be the foremost researcher and contributor to the systematic approach to instructional design and training. Gagne and his followers are known as behaviourists, and their focus is on the outcomes - or behaviours - that result from training [4]. After two semesters of using this Easy-to-Read textbook for conducting the course at this centre, a positive improvement to students’ results was observed. This paper analyses students’ results for the course at IIUM before the introduction of the Easy-to-Read textbook and after it was introduced. Results from survey conducted on the students in evaluating the effectiveness of Gagne’s Instructional Design approach used in the Easy-to-Read textbook, will also be tabulated and discussed. At the end of this paper, suggestions for further improvement to the Easy-to-Read textbook will be provided as a continuous effort to enhance students’ learning experience in C Programming course.